Inflammatory Determinants of Differential Tuberculosis Risk in Pre-Adolescent Children and Young Adults - Baguma, Richard; Mbandi, Stanley Kimbung; Rodo, Miguel J.; Erasmus, Mzwandile; Day, Jonathan; Makhethe, Lebohang; de Kock, Marwou; van Rooyen, Michele; Stone, Lynnett; Bilek, Nicole; Steyn, Marcia; Africa, Hadn; et al. (Frontiers in Immunology, 2021)
The risk of progression from Mycobacterium tuberculosis (M.tb) infection to active tuberculosis (TB) disease varies markedly with age. TB disease is significantly less likely in pre-adolescent children above 4 years of age than in very young children or post-pubescent adolescents and young adults. We hypothesized that pro-inflammatory responses to M.tb in pre-adolescent children are either less pronounced or more regulated, than in young adults. Inflammatory and antimicrobial mediators, measured by microfluidic RT-qPCR and protein bead arrays, or by analysing published microarray data from TB patients and controls, were compared in pre-adolescent children and adults. Multivariate analysis revealed that M.tb-uninfected 8 year old children had lower levels of myeloid-associated pro-inflammatory mediators than uninfected 18 year old young adults. Relative to uninfected children, those with M.tb-infection had higher levels of similar myeloid inflammatory responses. These inflammatory mediators were also expressed after in vitro stimulation of whole blood from uninfected children with live M.tb. Our findings suggest that myeloid inflammation is intrinsically lower in pre-pubescent children than in young adults. The lower or more regulated pro-inflammatory responses may play a role in the lower risk of TB disease in this age group.